Tele-Critical Care: An Update From the Society of Critical Care Medicine Tele-ICU Committee*. Issue 4 (April 2020) - Subramanian, Sanjay; Pamplin, Jeremy C.; Hravnak, Marilyn; Hielsberg, Christina; Riker, Richard; Rincon, Fred; Laudanski, Krzysztof; Adzhigirey, Lana A.; Moughrabieh, M. Anas; Winterbottom, Fiona A.; Herasevich, Vitaly
Abstract : Objectives: In 2014, the Tele-ICU Committee of the Society of Critical Care Medicine published an article regarding the state of ICU telemedicine, one better defined today as tele-critical care. Given the rapid evolution in the field, the authors now provide an updated review. Data Sources and Study Selection: We searched PubMed and OVID for peer-reviewed literature published between 2010 and 2018 related to significant developments in tele-critical care, including its prevalence, function, activity, and technologies. Search terms included electronic ICU, tele-ICU, critical care telemedicine, and ICU telemedicine with appropriate descriptors relevant to each sub-section. Additionally, information from surveys done by the Society of Critical Care Medicine was included given the relevance to the discussion and was referenced accordingly. Data Extraction and Data Synthesis: Tele-critical care continues to evolve in multiple domains, including organizational structure, technologies, expanded-use case scenarios, and novel applications. Insights have been gained in economic impact and human and organizational factors affecting tele-critical care delivery. Legislation and credentialing continue to significantly influence the pace of tele-critical care growth and adoption. Conclusions: Tele-critical care is an established mechanism to leverage critical care expertise to ICUs and beyond, but systematic research comparing different models, approaches, and technologies is still needed.